Center Volume Is Associated With Outcome After Pancreas Transplantation Within the Eurotransplant Region - Wouter H. Kopp; Marieke van Meel; Hein Putter; Undine Samuel; Helmut Arbogast; W. Schareck; Jan Ringers; Andries E. Braat (2016)
In Brief Background Outcome after surgery depends on several factors, among these, the annual volume-outcome relationship. This might also be the case in a highly complex field as pancreas transplantation. No study has investigated this relationship in a European setting. Methods All consecutive pancreas transplantations from January 2008 until December 2013 were included. Donor-, recipient-, and transplant-related factors were analyzed for their association with patient and graft survivals. Centers were classified in equally sized groups as being low volume (<5 transplantations on average each year in the 5 preceding years), medium volume (5-13/year), or high volume (≥13/year). Results In the study period, 1276 pancreas transplantations were included. Unadjusted 1-year patient survival was associated with center volume and was best in high volume centers, compared with medium and low volume: 96.5%, 94% and 92.3%, respectively (P = 0.017). Pancreas donor risk index (PDRI) was highest in high volume centers: 1.38 versus 1.21 in medium and 1.25 in low volume centers (P < 0.001). Pancreas graft survival at 1 year did not differ significantly between volume categories: 86%, 83.2%, and 81.6%, respectively (P = 0.114). After multivariate Cox-regression analysis, higher PDRI (hazard ratio [HR], 1.60; P < 0.001), retransplantation (HR, 1.91; P = 0.002), and higher recipient body mass index (HR, 1.04; P = 0.024) were risk factors for pancreas graft failure. High center volume was protective for graft failure (HR, 0.70; P = 0.037) compared with low center volume. Conclusion Patient and graft survival after pancreas transplantation are superior in higher volume centers. High volume centers have good results, even though they transplant organs with the highest PDRI. Outcome following surgery depends on several factors, amongst these the annual volume-outcome relationship. Patient and graft survival following pancreas transplantation are superior in higher volume centers. High volume centers have good results, even though they transplant organs with the highest pancreas donor-risk index.